436PAssessing the quality of life of Filipino cancer patients: A survey of Filipino oncologists. (24th November 2019) - Ting, F I L; Callueng, J M; Vallente, J; Hurtado, R A; Ramirez, A; Catedral, L I; King, R E; Mondragon, K A; Velasco, R; Ignacio, J; Ngelangel, C
Abstract: Background: With the advent of personalized medicine, recent clinical trials have placed much emphasis on the OS and PFS of cancer patients. However, several international guidelines also emphasize the need for assessing the Health Related Quality of Life (HRQoL) as part of our holistic approach in the management of cancer patients. This study evaluated the present status of the Filipino oncologists' approach in assessing the quality of life of cancer patients. Methods: This was a cross-sectional study that utilized a survey questionnaire. Participants included physicians in the care of the cancer patient (consultants & trainees) – medical, surgical, radiation, gynecologic oncologists, and hematologists, who were contacted via email through the database of their respective societies, and personally during scientific meetings / conferences. Descriptive and multivariate analysis were used to analyze the data. Results: 312 oncologists participated. 96% reported that HQRoL assessment was important for clinical work, however 58% perceived HRQoL to be a vague term; 69% agreed that verbal HRQoL assessments were generally enough, and 39% reported that their patients did not accept HRQoL questionnaires. Furthermore, 78% did not know which HRQoL assessment tool to use, and that the questionnaires were too extensive and too lengthy for routine use; 55% reported that they did not feel sufficiently trained to assess HRQoL. About 89.42% reported that they will be more confident if local HRQoL assessment guidelines will be present, and 92.95% agreed to the use of a unified HRQoL assessment tool for Filipino cancer patients. Conclusions: Filipino oncologists perceived HRQoL patient assessments to be important in clinical practice. However, majority did not know which tool to use and did not feel sufficiently trained to assess HRQoL. The creation of a practice guideline that would facilitate the use of a unified HRQoL assessment tool (containing 5-15 questions) for Filipino cancer patients will be explored. Legal entity responsible for the study: The Authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.